2017
DOI: 10.5812/intjsh.12918
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Parenting Styles, Self-compassion and Emotional Intelligence and Antisocial Behaviors in Students

Abstract: Background: According to the observations, antisocial behaviors are among major behaviors among male and female students. People with antisocial behaviors suffer from problems with respect to the quality of life. Objectives: The present study aimed to determine the relationship between parenting styles, self-compassion, and emotional intelligence with antisocial behaviors in students. Methods:The population included all students in Shiraz, Iran in the academic year of 2016. The sample was comprised of 148 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…Finally, while previous research seems to indicate that permissive parenting may be regarded as a predictor of antisocial behaviors (Zareian et al, 2017), we found no relationship between the latter and peace attitudes.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Finally, while previous research seems to indicate that permissive parenting may be regarded as a predictor of antisocial behaviors (Zareian et al, 2017), we found no relationship between the latter and peace attitudes.…”
Section: Discussioncontrasting
confidence: 97%
“…They observed that having at least one authoritative parent was associated with a lower frequency adolescent involvement in delinquent acts and that the child's level of delinquency was associated to the style exhibited by the one parent when the other parent exhibits a neglectful style. Furthermore, research shows that authoritarian and permissive parenting styles can be regarded as predictors of antisocial behaviors together with low self-compassion and emotional intelligence (Zareian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Zareian et al [18] found that authoritarian and permissive parenting styles and emotional intelligence were among the most significant predictors of antisocial behavior. They also found that youth raised with these two parenting styles are more likely to develop antisocial behaviors, and that antisocial youth exhibit lower emotional intelligence.…”
Section: H3mentioning
confidence: 99%